Pengaruh Bilingualisme dalam Bahasa Indonesia - Rakhmat, Moh.; Qohar, Hendri Abdul (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
Bilingualism is an increasingly common phenomenon in Indonesia due to globalization and technological development, which accelerates cross-language interaction and affects the structure of Indonesian in various aspects. One of the impacts is the increasing use of foreign words, especially English, which can enrich vocabulary but also risk replacing Indonesian equivalents. This study aims to analyze the impact of bilingualism on the development of the Indonesian language, both in terms of vocabulary, syntax, and morphology, and identify strategies that can be used to maintain a balance between the acceptance of foreign elements and the preservation of the Indonesian language. This research uses a qualitative method with a descriptive-analytical approach. The results show that bilingualism contributes to the linguistic development of society, but also causes interference that affects the structure of Indonesian. In the academic realm, bilingualism without a clear strategy can hinder understanding of the material. In digital communication, the phenomenon of code-switching and code-mixing is increasingly prevalent, especially among Generation Z, which shows the integration of bilingualism in their linguistic identity. Therefore, linguistic policies are needed that support a balance between the acceptance of foreign elements and the preservation of the Indonesian language so that bilingualism remains an enriching asset without threatening the sustainability of the national language.